Video animation as teaching aid for engineering drawing course in Malaysia vocational college - Ismail, Mohd Erfy; Ismail, Irwan Mahazir; Razali, Nizamuddin (2017)
The rapid development of information and communications technology (ICT) today has given a new breath to use of computer in education. One of the increasingly popular nowadays is a multimedia technology that merges a variety of media such as text, graphics, animation, video and audio controlled by a computer. With this technology, a wide range of multimedia software can be developed to improve the quality of education. This study aims to develop a multimedia educational animated video based interactive teaching and learning theory and design appropriate for Engineering Drawing subject in the title of Orthographic Projection according to the syllabus of Malaysia Vocational College. This research involved 30 respondents from Industrial Machining students in Vocational College. The research design was conducted by simple survey to collect data from the respondents. The instruments used in the form of a questionnaire to obtain information. Data was collected and analyzed using SPSS (Statistical Package for the Social Sciences) version 24. The study found that the interactive multimedia materials that have visual graphics, text, audio, video and animation, capable of increasing the rate of their acceptance more than 30% compared to using traditional learning methods.